PHYTOTOMASS OF ROBINIA PSEUDOACACIA L. TRUNK COMPONENTS IN THE PLANTED BLACK LOCUST STANDS WITHIN NORTHERN STEPPE ZONE OF UKRAINE - Sytnyk, S. A. (Forestry and Forest Melioration, 2018)
Introduction Determining the ecological and economic significance of forests at the global and regional levels requires multipurpose study at the local level. Estimation of the phytomass of the main forest forming species offers much scope for the research of ecosystem services of forests and their role in the formation of the resource base of wood and non-wood resources of the forest. Study of the components of above-ground phytomass of black locust trees will allow the estimation of phytomass of the robinia stands in the Northern Steppe of Ukraine, where the species forms predominantly pure plantations of protective purpose. The biological productivity of forest tree species by the components of above-ground phytomass was investigated in the numerous studies including works of Prof. Lakyda’s scientific school. However, the structure of aboveground phytomass and its dependence on the main mensuration characteristics of black locust trees in steppe stands have not been reported before. The purpose of the research is to develop the comprehensive regulatory and information framework for the estimation of trunk phytomass of black locust trees forming forest stands in the Steppe zone of Ukraine. Materials and Methods The study of trunk phytomass components for black locust trees included following three stages: the collection and processing of experimental data; the modeling of the volume of trunk phytomass components; the development and verification of normative and information framework. The experimental data for this study are an integral part of the study of the biological production of black locust trees and black locust forest stands within the Northern Steppe zone in Ukraine. The data were collected on twenty temporary plots established in plantations of forest enterprises subordinated to the State Agency for Forest Resources within the Dnipropetrovsk region. Indicators of the operational data set for sample trees, namely the age, trunk diameter at breast height 1.3 m (DBH), height, volume of the trunk wood, volume of the trunk bark, and volume of the trunk in the bark, were the subjects to correlation analysis. Results According to the correlation analysis, the components of the black locust trunk volume have reliable direct strong and moderate correlations with the basic biometric indicators of trees, namely age, DBH and tree height. Further studies of the phytomass of the trunk of black locust trees were carried out on the basis of simulation of its components. At the same time, different combinations of biometric indicators were used as impact factors. The calculated and proposed mathematical models for estimating the phytomass of the trunk have high values of the determination coefficients (Q? = 0,94…0,99) allowing their effective application for estimation of black locust trees, which formed forest stands in the conditions of the Northern steppe of Ukraine. Trunk phytomass increased in for a constant diameter at an altitude of 1.3 m with an increase in height, which. This was predicted during the analysis of the mathematical models, on the basis of which the calculations were carried out. Conclusions The developed normative reference data can be used for theoretical and practical purposes during forest inventory, for calculations on forest use targeting integral management of black locust stands and for the study of ecological functions of forests including integrated assessment of the above-ground phytomass of black locust trees and stands. 1 Fig., 9 Tables, 11 Refs.